Why do we not stand up to misinformation? Factors influencing the likelihood of challenging misinformation on social media and the role of demographics - Selin Gurgun (17416359) (2023)
This study investigates the barriers to challenging others who post misinformation on social media platforms. We conducted a survey amongst U.K. Facebook users (143 (57.2 %) women, 104 (41.6 %) men) to assess the extent to which the barriers to correcting others, as identified in literature across disciplines, apply to correcting misinformation on social media. We also group the barriers into factors and explore demographic differences amongst them. It has been suggested that users are generally hesitant to challenge misinformation. We found that most of our participants (58.8 %) were reluctant to challenge misinformation. We also identified moderating roles of age and gender in the likelihood of challenging misinformation. Older people were more likely to challenge misinformation compared to young adults while, men demonstrated a slightly greater likelihood to challenge compared to women. The 20 barriers influencing the decision to challenge misinformation, were then grouped into four main factors: social concerns, effort/interest considerations, prosocial intents, and content-related factors. We found that, controlling for age and gender, “social concerns” and “effort/interest considerations” have the significant impact on likelihood to challenge. Identified four factors were analysed in terms of demographic differences. Men ranked “effort/interest considerations” higher than women, while women placed higher importance on “content-related factors”. Moreover, older individuals were found to be more resilient to “social concerns”. The influence of educational background was most prominent in ranking “content-related factors”. Our findings provide important insights for the design of future interventions aimed at encouraging the challenging of misinformation on social media platforms, highlighting the need for tailored, demographically sensitive approaches. Other Information Published in: Technology in Society License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.techsoc.2023.102444